Comparative Study of Wavelet Image Compression: JPEG2000 Standart - Ansam Ennaciri; Mohammed Erritali; Mustapha Mabrouki; Jamaa Bengourram (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The objective of this paper is to study the main characteristics of wavelets that affect the image compression by using the discrete wavelet transform and lead to an image data compression while preserving the essential quality of the original image. This implies a good compromise between the image compression ratio and the PSNR (Peak Signal Noise Ration).